LINGUISTIC ТERMINOLOGY IN THE WORK BY YEVHEN TYMCHENKO “NOMINATIVE AND DATIVE IN THE UKRAINIAN LANGUAGE” - Ципердюк, О. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the linguistic terminology in the work by Yevhen Tymchenko “Nominative and Dative in the Ukrainian Language” published in 1925. Special attention is paid to the grammatical terms, which do not coincide with the ones established in the modern Ukrainian linguistics and are of Ukrainian origin.